Zakład ateisty — współczesna odpowiedź na argumentację Pascala - Wójtowicz, Marek (Folia Philosophica, 2018)
Pascal’s Wager is one of those philosophical issues which keep provoke reflection and searching for their new interpretations. It might be claimed that the argument from the well-known fragment of Pensées draws the reader’s attention first of all thanks to radicalism of its ultimate conclusion (“The faith in God is the only rational human attitude”). For more than 300 years new arguments for and against the premises, the argument and the conclusion of the wager have been formulated. Recently a strong trend towards formulating new arguments for or against God’s existence or rationality of theism, which make a reference to Pascal’s Wager, might be observed. One of the arguments made is the Atheist’s Wager, usually ascribed to Michael Martin, although its sources might be found in some of ancient philosophers. This argument, just as the one by Pascal, analyses the consequences of two opposite attitudes towards God’s existence. However, the conclusion of Atheist’s Wager (“Atheism is more rational than theism”) is just opposite to the one of Pascal’s argument. It is important to notice that there are various variants of Atheist’s Wager in which different aspects of the problem of rationality of theism and atheism are emphasized.